2022
DOI: 10.1097/md.0000000000029382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nighttime and daytime operation on outcomes of supracondylar humeral fractures: A prospective observational study

Abstract: Supracondylar humeral fractures are seen in children and treatment is usually closed reduction and percutaneous pinning (CRPP). This surgery can be performed at night, depending on its urgency. Fatigue and sleep deprivation can impact performance of doctors during night shifts. The purpose of this study is to investigate the association between night shifts postoperative morbidity and mortality of supracondylar fracture operations compared to daytime procedures.This prospective observational study included 94 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A study in thoracic surgery found that lung resections performed using a video-assisted thoracoscopic surgery approach (VATS) had a significantly higher incidence of intraoperative complications when performed during the night shift [ 51 ]. In a study by Buget et al of children operated on for supracondylar humerus fracture, better outcomes were found with daytime operations, with shorter operative time and lower morbidity than with nighttime operations [ 52 ]. Studies in various fields of abdominal surgery again supported the safety of daytime surgery [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in thoracic surgery found that lung resections performed using a video-assisted thoracoscopic surgery approach (VATS) had a significantly higher incidence of intraoperative complications when performed during the night shift [ 51 ]. In a study by Buget et al of children operated on for supracondylar humerus fracture, better outcomes were found with daytime operations, with shorter operative time and lower morbidity than with nighttime operations [ 52 ]. Studies in various fields of abdominal surgery again supported the safety of daytime surgery [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reported data regarding the relative quantity of incidents occurring during different times of the day was collected as an additional parameter and cannot be used to draw any conclusions on this matter. Studies with methodology focused on this question report a higher rate of perioperative adverse events during nighttime surgery [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%